Risk assessment of choledocholithiasis prior to laparoscopic cholecystectomy and its management options. Issue 3 (April 2018) - Aleknaite, Ausra; Simutis, Gintaras; Stanaitis, Juozas; Valantinas, Jonas; Strupas, Kestutis
Background: Accurate risk evaluation of choledocholithiasis prior to laparoscopic cholecystectomy is essential to determine optimal management strategy. Objective: Our study aimed to evaluate the accuracy of separate predictors and Vilnius University Hospital Index (VUHI = A/30 + 0.4 × B; A = total bilirubin concentration (µmol/l), B = common bile duct (CBD) diameter (mm) measured by ultrasound) diagnosing choledocholithiasis and to assess different management strategies (cholecystectomy with intraoperative cholangiography and endoscopic retrograde cholangiopancreatography (ERCP)). Methods: The retrospective study included 350 patients admitted to a tertiary care centre for laparoscopic cholecystectomy for cholecystolithiasis who were investigated for concomitant choledocholithiasis. Results: Choledocholithiasis was diagnosed in 182 (76.2%) cases in the high-risk group (VUHI value ≥4.7) and 44 (39.6%) in the low, odds ratio is 4.86 (95% CI: 3.00–7.88). Its sensitivity was 80.5%, specificity 54.0%, accuracy 71.1%. Dilated CBD had the highest sensitivity (92.5%) of predictors. ERCP showed better diagnostic performance than intraoperative cholangiography. Complications of ERCP were more frequent for patients without stones. There was no significant difference of outcomes between the two management strategies. Conclusion: The prognostic index has good diagnostic accuracy but dividing patients into two risk groups is insufficient. The suggested model allows determining an intermediate-risk group, which requires additional investigation. Both management approaches are appropriate.